2019
DOI: 10.1007/s12524-018-0926-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Spectral Index for Detection of Orange Spotting Disease in Oil Palm (Elaeis guineensis Jacq.) Using Red Edge and Neural Network Techniques

Abstract: Spectral screening can play an important role in successful detection of viroid-infected oil palm seedlings from nursery stage prior to transplanting into the field. Coconut cadangcadang viroid (CCCVd) is the main causal agent of orange spotting (OS) disease. OS disease is an emerging disease in Malaysian plantation. In this study, a glasshouse experiment was conducted with fifteen CCCVd-inoculated and five healthy oil palm seedlings in the growing season of 2015. Spectral screening was performed using a hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The reviewed works prove the possibility of detecting oil palm [36,[50][51][52][53][54][55][56][57][63][64][65][66], citrus [73][74][75][76][77][78], Solanaceae family crops [91][92][93][94][95][96][97][98][99][100][101][102][103] and wheat [24,[124][125][126][127][128][129][130][131][132][140][141][142][143][144][145] diseases using HRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed works prove the possibility of detecting oil palm [36,[50][51][52][53][54][55][56][57][63][64][65][66], citrus [73][74][75][76][77][78], Solanaceae family crops [91][92][93][94][95][96][97][98][99][100][101][102][103] and wheat [24,[124][125][126][127][128][129][130][131][132][140][141][142][143][144][145] diseases using HRS.…”
Section: Discussionmentioning
confidence: 99%
“…On the subject of OS, the authors conducted and published a number of studies on SVI and ANN choice for disease determination, as well as chlorophyll content at the leaf scale of the diseased plants. The hyperspectral data of OS diseased and healthy oil palm seedlings was processed by five different ANNs for evaluation of four red-edge indices followed by the selection of spectral bands from the red edge (680-780 nm), with a result that a red-edge inflection point (at 700 nm) could serve as a good indicator of the plant stress caused by OS in oil palm seedlings [65,66]. A systematization of the reviewed materials is present in Table 1.…”
Section: Hyperspectral Remote Sensing Of Oil Palm Diseasesmentioning
confidence: 99%
“…By analyzing the reflectance spectra of oil palm seedlings and healthy oil palm seedlings inoculated with coconut cadang-cadang viroid (CCCVd), it was shown that the infrared inflection point (ReIP) at 700 nm could well reflect the condition of oil palm seedlings under CCCVd stress. The dual-band enhanced vegetation index (EVI2) is the best spectral index for detecting orange spot disease in mature oil palm forests [84]. Zhang et al [85] used a loop-mediated isothermal amplification technique to develop a rapid and sensitive detection method for oil palm damping-off bacteria and designed a total of 6 primers based on 8 loci in the ITS region gene.…”
Section: Detection Technology For Oil Palm Disease Resistancementioning
confidence: 99%
“…ANNs have been used successfully in many studies for the identification and classification of various plant stresses. These include detecting powdery mildew and soft rot in zucchini [129], classifying biotic stresses in pomegranate [106], detecting orange spotting disease in oil palm [130], and identifying crown rot in wheat [131]. A major advantage of ANNs is their ability to be used without specialized knowledge on the data and its interpretation; however, disadvantages include being prone to overfitting and requiring greater amounts of computational resources [132].…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%